Pengaruh Iklan Berdasarkan Konsep Aida Terhadap Keputusan Pembelian Sabun Mandi Lifebouy (Studi Kasus Pada Warga Depok - Jawa Barat) - Nurmin Arianto (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2019)
Based on the Top Brand Index data for the 4th consecutive Lifebuoy soap brand, the fluctuation was due to the Desire of Depok residents to buy Lifebuoy brand bath soap, which is still lacking. This study aims to determine the effect of attention, interest, Desire, action, on purchasing decisions. This research was conducted on Depok city residents with incidental sampling technique where 100 respondents obtained the sample. Using the instrument test data analysis, the classical assumption test, and multiple linear regression. From the results of the regression analysis obtained: Y = 14,010 + 0,296 X1 + 0,171 X2 + 0,246 X3 + 0,163 X4 + e and the calculated t value for each significant variable where attention, interest, desire and action partially have a significant effect on purchasing decisions. Furthermore, F arithmetic obtained results of 6.394 and significant so that the variables of Attention, Interest, Desire, and action together have a significant influence on purchasing decisions. The value of determination c obtained 0.197 results coefficient, which means that 17.9% of purchasing decisions are influenced by the variables of attention, interest, desire, and action, and the remaining 82.1% are influenced by other variables not examined, such as product quality, price, and others. Furthermore, the most influential variable on purchasing decisions is Desire (Desire), which has a greater t value of 2.958> 1.985.